The answer to this question would be 6
Answer:
4 cups
Step-by-step explanation:
because if you have 2 cups for a half a quart then add another half which means add 2 more cups 2+2=4 cups
Answer:
Step-by-step explanation:
5(x-3y)+2(4x+y)-(x+y)
5x-15y+8x+2y-x-y
5x+8x-x-15y+2y-y
13x-x-13y-y
12x-12y
Answer:
Step-by-step explanation:
x2+y2+ax+by+c=0
Step 1: Add -by to both sides.
ax+by+x2+y2+c+−by=0+−by
ax+x2+y2+c=−by
Step 2: Add -x^2 to both sides.
ax+x2+y2+c+−x2=−by+−x2
ax+y2+c=−bax+y2+c+−y2=−by−x2+−y2
ax+c=−by−x2−y2
Step 4: Add -c to both sides.
ax+c+−c=−by−x2−y2+−c
ax=−by−x2−y2−c
Step 5: Divide both sides by x.
ax
x
=
−by−x2−y2−c
x
a=
−by−x2−y2−c
x
y−x2